Formulation and characterization of nanoemulgel of ethanol extract of bay leaves (Syzygium polyanthum) as an anti-burn agent using the hot plate method using white wistar rats - Ningrum, Windi Pratama; Jafar, Garnadi; Pramudiahwardani, Ananda Rota; Kusriani, Herni (Institute of Computer Science (IOCS), 2025)
Introduction: Wounds are tissue damage that can cause functional disorders and risk of infection. Effective wound management is essential to accelerate tissue regeneration and prevent complications. Bay leaf extract (Syzygium polyanthum) contains bioactive compounds such as flavonoids, tannins, and saponins that have anti-inflammatory, antibacterial, and wound healing activities. However, the limited bioavailability and skin penetration of these active compounds are challenges in topical therapy. Objective: This study aims to develop and evaluate a topical drug delivery system based on bay leaf extract nanoemulsion as an alternative therapy to accelerate wound healing. Method: Extraction was carried out using ethanol solvent, then formulated into a nanoemulsion with oil, surfactant, and co-surfactant components. Formulation characterization was carried out by measuring particle size, polydispersity index, zeta potential, and physical stability tests. Evaluation of effectiveness was carried out using a wound model in Wistar rats with the hot plate induction method. Wound healing observations were carried out clinically and histologically for a period of 14 days. Results: The formulation results showed that the nanoemulsion had a particle size of <200 nm, PDI <0.5, and zeta potential of ±25 mV, indicating good physical stability. Burn activity tests showed that topical administration of bay leaf extract nanoemulsion accelerated wound contraction, increased epithelialization, and improved tissue structure compared to the control group. Conclusion: Bay leaf extract can be formulated in a nanoemulsion-based nanoparticle delivery system that shows stable physical characteristics and is effective in accelerating wound healing.